PENGARUH SUPERVISI AKADEMIK KEPALA SEKOLAH DAN MOTIVASI GURU TERHADAP KINERJA GURU DI SDN - Murita, Murita; Aswandi, Aswandi; Radiana, Usman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe implementation of academic supervision is done routinely and continuously will enable the improvement of teacher performance which ultimately have an impact on improving student's learning achievement also. Factors influencing teacher performance in this research are academic supervision and Teacher Work Motivation of principal. The problems in this study are as follows: 1) What is the description of the principal academic supervision, teacher work motivation, and teacher performance? 2) Does the principal's academic supervision affect teacher performance? 3) Does teacher work motivation affect teacher performance? 4) Does the teacher's academic supervision and work motivation jointly affect teacher performance?This research generally aims to reveal the influence of academic supervision and teacher work motivation on the performance of SDN teachers in Kecamatan Selakau Sambas District. This research uses quantitative approach. The data used is quantitative data. The population in this study amounted to 215 teachers. While the sample amounted to 140 teachers. Data were collected using questionnaires by measurement model using Likert scale. The collected data is tabulated. Then performed an analysis using the help of computer application program, namely SPSS version 16 for Window. Data analysis uses descriptive statistics and inferential statistics. The first step in conducting hypothesis testing, namely test requirements regression analysis (normality test and linearity test). After the analytical requirements test is met, the next is hypothesis testing. The analysis technique used is multiple regression analysis. To know the effect of free variable to the dependent variable simultaneously used F test.Key Words: Principal Academic Supervision, Teacher Motivation, Teacher Performance